An investigation and analysis of the role of strategic entrepreneurship on business development - MolkAra, Melika (International Journal of Business Management and Entrepreneurship, 2022)
The inclination to entrepreneurship is an approach to prompt development in an organization through novel products, newborn processes and innovative strategies. The link between strategy and entrepreneurship, which is referred to as strategic entrepreneurship, is the basis of entrepreneurial success in organizations. Strategic entrepreneurship is the result of making a balance between two related and continuous actions, i.e., opportunistic actions and advantage-seeking actions. Strategic entrepreneurship is considered as the application or stimulation of entrepreneurial activities to achieve strategic purposes. Strategic entrepreneurship benefits to increase company performance and develop sustainable competitive advantage through entrepreneurial activities with a strategic perspective. Thus, strategic entrepreneurship is a necessity for businesses in order to generate maximum revenue.